Do smoking bans always hurt the gaming industry? Differentiated impacts on the market value of casino firms in Macao - Jing Hua Zhang; Kwo Ping Tam; Nan Zhou (Economics: The Open-Access, Open-Assessment E-Journal, 2016)
The gaming economy has expanded rapidly in East Asia over the past decade. Despite the known public health hazards of secondhand smoking, smoking bans in casinos remain controversial due to concerns over the potential economic harm to casino firms. Applying an event study, the authors examine the abnormal returns of casino stocks in response to three unexpected smoking ban announcements from 2011 to 2015 in Macao. Their analysis reveals that these announcements were associated with differentiated abnormal returns of casino stocks. Stocks of traditional casinos suffered abnormal losses of 0.58-3%, while the Las Vegas themed casinos enjoyed positive abnormal returns of up to 3%. Furthermore, the authors find that low air quality in gaming venues and high dependence on gaming revenues are associated with abnormal losses, while positive management initiatives are significantly correlated with positive abnormal returns. The findings of this study provide a full picture of the impacts of smoking bans on casinos and thus will be a useful policy references for the Macao government, as well as for the rapidly growing gaming industry in Asia and developing economies elsewhere.
Keywords: L83; K32; Z33; 330; smoking bans; economic impacts; casinos; abnormal returns; Macao